Review on nutritional content and pharmacological activities in leaves of barringtonia species (Barringtonia acutangula L. and Barringtonia racemosa L.) / Noor Nazzatul Syazana Mohammad Zamri and Nur Aisyah Ismail - Mohammad Zamri, Noor Nazzatul Syazana; Ismail, Nur Aisyah (2021)
Barringtonia species have enormous potential for complementary and medicinal uses, however, the uses of the species are underutilised and limited research. Each part of this species has their own functionality; however, this review only focused on the leaves as the leaves of the species can be consumed as ulam. It also contains high total phenolic content and exhibits antioxidant activity. It is aimed to provide a clearer explanation and information regarding these species. The review discussed two species which are B. acutangula and B. racemosa and made a comparison between the proximate analysis and the phytochemical content in the leaves of the plants. The approximate percent composition of moisture (70.52%), ash (0.96%), fibre (1.38%), protein (2.54%) and carbohydrate (25.71%) in B. racemosa while for B. acutangula, only carbohydrate (9.85%), protein (13.13%) and ash (7.7%) were analysed quantitatively. Phytochemicals present in these plants are collected from current studies and reported B. racemosa have higher content in total phenolic content (1585.20 mg/g) and total ascorbic acid (88.9 mg/g). Meanwhile, B. acutangula reported to have higher content in total flavonoid (109.52mg/g) and total tannin (105.52 mg/g). The review also comprised pharmacological activities in the Barringtonia species, particularly, antioxidant, antibacterial and antidiabetic activities, from current documented literatures to provide significant information on the nutritional benefits of Barringtonia species. This review proved the needs for future research and commercialisation on this species due to the abundance of sources and nutritional content especially in making it as future medicine for Malaysians.